Safavid Lusterware: Recognition of Form, Design and Production Centers - Hashem Hosseini; Farzaneh Farrokhfar (نگره, 2022)
Throughout the history of pottery and among all the methods of pottery decoration, lusterwares, because of their shine and their gold-like reflection, have always been the subject of attention and admiration for everybody. Lustre is a metal glass nanocomposite thin layer made of metal in a silica-based glassy matrix. The lustre technique was first applied to glass objects in early Islamic Egypt and later to glazed ceramics in other Islamic lands, especially in Iraq and Iran. Lusterwares are one of the most beautiful types of ceramics in the history of Islamic pottery that the peak period of its popularity in Iran is related to the Seljuk era until the end of the Mongol period. The Luster masterpieces that are from the Seljuk, Mongol and Ilkhanid eras and even the Timurid era, represent the peak of using of decorative techniques to build the potteries. For some reason, this technique has become obsolete in the Timurid period and has been revived with the advent of the Safavid dynasty and has been produced with new features.Unlike the examples of the Islamic Middle Ages in Iran, there is little information about Safavid lusterwares, especially in the fields of shapes and forms, decorative patterns and the main centers for making luster, which raises the need for scientific research in this field. The aim of this study is to identify, classify and analyze the most important formal features and decorative motifs of these luster ceramics in accordance with the opinions of Islamic pottery researchers and to suggest areas as their manufacturing centers according to these characteristics. Accordingly, the research questions are: What are the features of forms and decorative patterns in lusterware ceramics in the Safavid era? And which areas were the main centers for the construction of these works? The research method is descriptive-analytical with a comparative approach and based on qualitative analysis. In this article, first, the information and images of a number of luster potteries of the Safavid era have been collected by using some electronic sources and library resources and then, 21 excellent luster ceramics of the Safavid era have been selected among the artworks in museums and collections for further study, taking into account the three factors: originality, quality and accessibility. After describing the formal characteristics and decorative patterns of the samples, the linear design of decorative patterns has been done to see more details. One of the limitations of the present study is the lack of access to many specimens and their specifications, which due to their location in the repository of domestic museums or outside the political and geographical borders of Iran, access to them or full photography and obtaining all dimensional details of them were not possible. Although many researches have been done about luster glaze ceramics in the Middle Ages, especially in the field of technique of making or laboratory examinations of glaze of this type of pottery or its decorative patterns, but about lusterwares in the Safavid era, limited research has been done and little information is available; most of which are repeated in different sources. According to the research findings, in terms of form, Tofdan and especially different types of Sorahi with small-sized designs are the most significant and special products of the Safavid era lusterwares. In terms of color quality, pottery is divided into three general categories: gold patterns on white background, gold patterns on azure background, and a combination of gold patterns on separate white and azure glazes, and in terms of the content of the designs, despite the influence of Chinese landscape making on the type and details of the designs and the style of execution, it shows independent methods. Also, the influence of Ottoman and Indian-Mughal art styles in the field of some decorative designs shows the artistic relations between the Safavid era Iran and these neighboring lands. The cities of Tabriz, Qazvin and Mashhad in the 16th century and the cities of Isfahan, Yazd and Kerman in the 17th century, are the most important areas in Iran that can be named as the centers of production of lusterwares ceramics in the Safavid era. In the end, it is reminded that the current research has been done according to the available samples and cannot claim to study all the dimensions of the Safavid era luster glaze, so, further research in this field seems necessary.